SIKAP ULAMA TERHADAP PENGGUNAAN CRYPTOCURRENCY DALAM MUAMALAH MODERN - Irshofa Hany; Nawal Ula Sakinah; Saadiyah Fajar; Fasta Nadiatul Ilmi; Nanang Hasan Susanto (Jurnal Al-Hikmah: Jurnal Dakwah, 2025)
Advances in digital technology have brought about major changes in the economic system, one of which is the emergence of cryptocurrency as a form of digital asset that is increasingly being used in transactions and investment activities. This development has elicited various responses among scholars, particularly regarding the legal status of cryptocurrency use in contemporary muamalah practices. This article aims to examine the views of Islamic scholars on cryptocurrency and the fiqh arguments used in assessing its compatibility with Islamic legal principles. This research is positioned as a normative study with a qualitative approach that focuses on the analysis of Islamic law through the examination of Islamic literature and applicable regulations. The research method used is a literature study by collecting and analysing various primary sources, such as the Qur'an, hadith, and fiqh books, as well as secondary sources in the form of scientific journals, fatwas from scholars, and laws and regulations related to crypto assets in Indonesia. The discussion was conducted by describing the differences in opinion among scholars regarding the nature of cryptocurrency, both those who consider it as valuable property that can be utilised in a sharia-compliant manner and those who assess that this asset contains elements of uncertainty and speculation that have the potential to violate the principles of muamalah. In addition, this article also discusses the role of state regulation and its relevance to sharia values, as well as placing maqashid sharia as an evaluative framework for assessing the benefits and potential losses of using cryptocurrency. The results of the study show that differences in opinion among scholars focus more on the patterns of use and transaction mechanisms of cryptocurrency, rather than solely on the form of the asset itself. Therefore, its use can be considered as long as it complies with the principle of prudence and does not conflict with the main objectives of Sharia.Keyword: cryptocurrency, contemporary muamalah, Islamic law, scholars' views, maqashid shariaKemajuan teknologi digital telah membawa perubahan besar dalam sistem ekonomi, salah satunya dengan hadirnya cryptocurrency sebagai bentuk aset digital yang semakin banyak dimanfaatkan dalam transaksi dan kegiatan investasi. Perkembangan ini memunculkan beragam respons di kalangan ulama, khususnya terkait penentuan status hukum penggunaan cryptocurrency dalam praktik muamalah kontemporer. Artikel ini bertujuan untuk mengkaji bagaimana pandangan ulama terhadap cryptocurrency serta dasar argumentasi fikih yang digunakan dalam menilai kesesuaiannya dengan prinsip-prinsip hukum Islam. Penelitian ini diposisikan sebagai kajian normatif dengan pendekatan kualitatif yang menitikberatkan pada analisis hukum Islam melalui penelaahan literatur keislaman dan regulasi yang berlaku. Metode penelitian yang digunakan adalah studi pustaka dengan menghimpun dan menganalisis berbagai sumber primer, seperti Al-Qur’an, hadis, dan kitab fikih, serta sumber sekunder berupa jurnal ilmiah, fatwa ulama, dan peraturan perundang-undangan terkait aset kripto di Indonesia. Pembahasan dilakukan dengan menguraikan perbedaan pendapat ulama mengenai hakikat cryptocurrency, baik yang menganggapnya sebagai harta bernilai yang dapat dimanfaatkan secara syar‘i maupun yang menilai bahwa aset tersebut mengandung unsur ketidakpastian dan spekulasi yang berpotensi melanggar prinsip muamalah. Selain itu, artikel ini juga membahas peran regulasi negara dan relevansinya dengan nilai-nilai syariah, serta menempatkan maqashid syariah sebagai kerangka evaluatif untuk menilai aspek kemaslahatan dan potensi kerugian dari penggunaan cryptocurrency. Hasil kajian menunjukkan bahwa perbedaan pandangan ulama lebih berfokus pada pola pemanfaatan dan mekanisme transaksi cryptocurrency, bukan semata-mata pada bentuk asetnya, sehingga penggunaannya dapat dipertimbangkan sepanjang memenuhi prinsip kehati-hatian dan tidak bertentangan dengan tujuan utama syariah. Kata Kunci: cryptocurrency, muamalah kontemporer, hukum Islam, pandangan ulama, maqashid syariah